Pre-service teachers’ investments in English and construction of professional identity in the Indonesian context - Marcelinus Pascalis Nue; Christine Manara (Studies in English Language and Education, 2022)
This study explored the pre-service teachers (PSTs) professional identity construction during their teacher education training at a private university in Central Java, Indonesia. It particularly investigated their understanding of the teaching profession and their professional identity, guided by two research questions: 1) what have been the influential aspects of the Indonesian pre-service teachers’ investment in the teaching profession? and 2) what professional identities do the PSTs (re)construct during their teacher education training? A qualitative case study was adopted as the design of this study. Data of this study were collected using an open-ended questionnaire and in-depth semi-structured interviews. Participants of this study are eleven PSTs of a private university in Central Java. The obtained data were analyzed by using the theoretical grounding of situated learning, professional identity, and investments. An interpretive approach and thematic analysis were adopted in coding and analyzing the PSTs’ open-ended questionnaire responses and narrative accounts obtained from the interviews. It is found that most aspects of PSTs’ construction of professional identity are their continuous learning participation and contemplation during their training in the English teacher education (ETE) program and their dynamic inner dialogue with their two selves (i.e. the student-self and the teacher-self) during the teaching practicum at school. These influential aspects lead to the emerging professional identity of the PSTs as caring, motivational, pleasant, and empathetic teachers. This result implies the need to emphasize the acquisition of teacher identity and reflective teaching at the heart of teacher education.